PERAN SUB-SEKTOR PERKEBUNAN PADA PEREKONOMIAN KABUPATEN INDRAGIRI HILIR PROPINSI RIAU - NIKEN NURWATI; ANTO ARIYANTO (Jurnal Ilmiah Pertanian, 2008)
ABSTRAKIn general this research aim to seeing and study common picture and directionof economics of Sub-Province Indragiri, Hilir, and also analyse interrelationshipof sub-sektor plantation with other sector. Peculiarly this purpose of research isfor: (1) analyst of role of sub-sektor plantation in economics structure in IndragiriHilir, (2) analyse interrelationship ( linkages) plantation sector with other sector,and (3) analyse coefficient and sensitivity of spreading of sub-sektor plantationin Indragiri Hilir.Region becoming this research object is economics of Sub-ProvinceIndragiri Hilir as a whole emphasizing at role of sub-sektor plantation in economicsof regional, and also interrelationship with other sectors. This thing based onreality that aspect of development of plantation of vital importance for Sub-Province Indragiri Hilir.Data which applied in this research is Tables Of Input-Output Sub-ProvinceIndragri Hilir year 2003 which based on is producer price transaction. Tables OfI-O 2003 is tables of I-O spent by Office Bappeda Kabupaten Indragiri Hilir whichcompiled with classification of 43 sector. Analysis result indicate that role of subsektorPlantation in Sub-Province Indragiri Hilir very dominant in structure ofeconomics of Sub-Province Indragiri, Hilir, especially at agrobisnis coconut. BasedOn Tables Of I-O Sub-Province Indragiri Hilir seen sector which including leadingsector that is coconut industrial sector and coconut.